2021
DOI: 10.1186/s12985-021-01691-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal hepatitis B virus carrier and gestational diabetes mellitus: a retrospective cohort analysis

Abstract: Introduction Given that many pregnant women have chronic hepatitis B virus (HBV) infection and that gestational diabetes mellitus (GDM) is linked to poor maternal and neonatal outcomes, we looked into the relationship between the hepatitis B surface antigen (HBsAg) and GDM to see if a high HBV DNA load is linked to a higher risk of GDM in chronic maternal HBsAg carriers. Materials and methods Our study included 39,539 pregnant women who gave birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The current study showed that the prevalence rate of HBsAg positivity in the study area was 11.74%, which was similar to that in Fujian (11.39%) 22 and Anhui (10.39%). 19 However, it was higher than that in Shaanxi (7.07%), 10 Guangdong (7.69%), 18 and Zhejiang (5.88%). 23 Similar to other reports, the prevalence of HBV infection was significantly lower in Liaoning (3.08%), 24 Tianjin (3.77%), 25 Shanxi (4.90%), 26 Xinjiang (4.43%), 26 Sichuan (4.24%), 27 and Yunnan (3.28%).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The current study showed that the prevalence rate of HBsAg positivity in the study area was 11.74%, which was similar to that in Fujian (11.39%) 22 and Anhui (10.39%). 19 However, it was higher than that in Shaanxi (7.07%), 10 Guangdong (7.69%), 18 and Zhejiang (5.88%). 23 Similar to other reports, the prevalence of HBV infection was significantly lower in Liaoning (3.08%), 24 Tianjin (3.77%), 25 Shanxi (4.90%), 26 Xinjiang (4.43%), 26 Sichuan (4.24%), 27 and Yunnan (3.28%).…”
Section: Discussionmentioning
confidence: 81%
“…There are numerous epidemiological studies about HBV among pregnant women in China. 18 , 19 Meizhou City is a remote mountainous region located in the northeast of Guangdong Province in Southern China, with an area of 15,876 square kilometers and a population of 5.43 million. It remains one of the most undeveloped regions in China due to its mountainous terrains coupled with a sparsely distributed population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic viral hepatitis has been associated with iron-overload and high serum hepcidin, a peptide hormone involved in the homeostasis of iron ( 38 ). Excess iron can directly affect insulin synthesis/secretion and enhance oxidation of free fatty acids, in turn decreasing glucose utilisation in muscles and promoting gluconeogenesis in the liver, ultimately leading to insulin resistance ( 39 ).…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Lao et al ( 2013 ) reported that HBV DNA was detected in 19.6% and 30.4% in the second and third trimesters respectively of HBsAg positive mothers without detectable HBV DNA in the first trimester ( 41 ). It has been hypothesised that positive maternal HBeAg status and high HBV viral load could incite a more vigorous immune response exacerbating inflammation thereby worsening insulin resistance, leading to GDM ( 4 , 6 , 7 , 14 , 39 ). However, with the exception of one study ( 39 ), recent literature exploring this proposition has largely shown no association ( 4 , 6 , 7 , 14 ).…”
Section: Possible Mechanismsmentioning
confidence: 99%